Does Stereotype Threat Affect Men in Language Domains? - Chaffee, Kathryn Everhart; Lou, Nigel Mantou; Noels, Kimberly A. (Frontiers in Psychology, 2020)
Boys and men tend to underperform in language education, and they are also underrepresented in language-related fields. Research suggests that stereotypes can affect students’ performance and sense of belonging in academic subjects and test settings via stereotype threat. For example, girls and women sometimes underperform on math tests following reminders that math is for boys. We sought to test whether stereotypes that women have better language skills than men would affect men. In a series of four experiments (N=542), we tested the effect of explicit stereotype threats on men’s performance in language-related tasks, and their sense of belonging to language-related domains. We found little evidence for stereotype threat effects on men in language. Bayesian analysis suggested that the null hypothesis was consistently more likely than the alternative, and mini-meta analyses showed effect sizes near zero. Future research should explore other explanations for gender gaps in language.